David Lynch’s Los Angeles: Control and Liberation through the Cinematic Image - Jakob Jurisch (IAFOR Journal of Cultural Studies)
Arguably, one of America’s greatest cinematic surrealists, David Lynch, boasts a filmography concerned with iconography, the nature of kitsch, and what dark underbellies such images veil. In Lynch’s famous TV series Twin Peaks (1990-2017), the kitsch aspect of a local small-town murder mystery is connected to a surreal and ungraspable larger world of primordial darkness and incomprehensible nightmares, where consciousness and unconsciousness constantly inform upon one another, one cannot exist without the other. Lynch’s cinematic outings, such as the neo-noir Lost Highway (1997), the acclaimed Hollywood fantasy Mulholland Drive (2001), and the experimental nightmare Inland Empire (2006), are all set in the heart of the film industry, in Los Angeles, and reveal his most ambitious vision yet: to examine the hierarchies of images in American pop-culture, providing a space in which dreams and nightmares routinely, yet subtly, intersect. In my article, I will analyze how these films take stock of American West Coast lives of the late 20th and early 21st century, on the one hand providing a psychodrama of dreams gone bust, while on the other exploring the potential for a new iconography.